Genotype Phenotype Correlation of Genetic Polymorphism of PPAR Gamma Gene and Therapeutic Response to Pioglitazone in Type 2 Diabetes Mellitus-A Pilot Study - S. Shanmuga Priya (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Pro12Ala polymorphism is a missense mutation at codon 12 in peroxisome proliferator-activated receptor γ gene (PPARG). This polymorphism is known to be associated with increased insulin sensitivity. Pioglitazone, a thiazolidinedione, is an anti-diabetic drug which acts as an agonist at PPAR γ receptor. Aim: To determine the association between Pro12Ala polymorphism of the PPARG and variation in therapeutic response to the PPARγ agonist, pioglitazone. Materials and Methods: The study was done as a hospital based pilot project in 30 patients with type 2 diabetes mellitus, on treatment with sulfonylurea or metformin but without adequate glycaemic control. They were started on pioglitazone as add on therapy for a period of 12 weeks. The participants were categorized as responders and non-responders based on the change in HbA1C level after 12 weeks. Pro12Ala polymorphism was analysed by polymerase chain reaction-restriction fragment length polymorphism. Statistical Analysis: Logistic regression analysis was done to evaluate the associations between age, baseline body weight, BMI, waist circumference, waist-hip ratio and Pro12Ala variants with the response to pioglitazone. The p-value< 0.05 was considered significant. Results: The frequency distributions of PPAR gamma genotypes were 80% for Pro/Pro and 20% for Pro/Ala in the study population. Among the study participants, 30% were nonresponders and 70% responders to pioglitazone. A significantly higher frequency of the polymorphism was detected in the responders (p=0.005) compared to non-responders group. Conclusion: Our study suggests that there is a potential association between Pro12Ala polymorphism and glycaemic response to pioglitazone.